Concern-sensitive navigation: Improving navigation in web software through separation of concerns - Nanard, Jocelyne (2008)
Traditionally, the use of good techniques to improve software modularity, such as advanced separation of concerns, has no impact in the user experience, for example while navigating Web software. While the intent of these techniques is to simplify evolution and maintenance, navigation design quality is often seen as an unrelated concern. In this paper we present a novel approach for improving navigation in Web applications by using some of the core application's concerns (called navigational concerns) to derive their navigational structure. Using some realistic examples we show that, by carefully using these concerns, we can improve the user experience. Some implementation issues are discussed and a thorough comparison with related ideas in the Web Engineering field is presented.